Efektifitas pemberian makanan tambahan lokal (PMT) terhadap kesejahteraan ibu hamil: Literature review - Damayanti, Melly; Aminin, Fidyah; Jannah, Rawdatul; Mukodri, Dewi Mey Lestanti; Saputri, Nurul Aini Suria; Jasda, Asmarita; Ikhwan, Zainul; Safitri, Tiyara; Putri, Sabtini Ika; Cintiani, Jeni Cesi (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Providing locally-based supplementary feeding has been proven effective in improving the health status of pregnant women and their babies while also supporting food sustainability and local economic development.Objectives: his article aims to explore the types and benefits of locally-based supplementary foods recommended during pregnancy through a literature review.Methods: This study employed a literature study design using the narrative literature review method by searching for scientific articles in the PubMed, ProQuest, and Google Scholar databases. A total of 26,194 articles were found, and 8 articles were analyzed. The article selection process followed the PRISMA standard guidelines. Articles published between 2015 and 2024 were included. The search was conducted using the keywords "local supplementary food," "pregnant women," "nutritional status," and "local PMT", then filtered based on the inclusion criteria: studies evaluating the effects of local supplementary feeding on the nutritional status of pregnant women, as well as the health status of both the mother and the newborn. Data were analyzed narratively to identify consistent findings.Results: The majority of studies show that locally-based local supplementary is effective in increasing weight gain during pregnancy, improving maternal upper arm circumference, and addressing pregnancy-related anemia Additionally, local supplementary has been shown to improve the health of newborns. However, nutrition education and counseling during pregnancy are essential to support better maternal health behaviors.Conclusion: Locally-based supplementary is effective in improving the nutritional and health status of both mothers and their babies. Moreover, it contributes to economic growth and food security.